2008
DOI: 10.5194/acp-8-91-2008
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of N<sub>2</sub>O<sub>5</sub> with mineral dust: aerosol flow tube and Knudsen reactor studies

Abstract: Abstract. The interaction of mineral dust with N 2 O 5 was investigated using both airborne mineral aerosol (using an aerosol flow reactor with variable relative humidity) and bulk samples (using a Knudsen reactor at zero humidity). Both authentic (Saharan, SDCV) and synthetic dust samples (Arizona test dust, ATD and calcite, CaCO 3 ) were used to derive reactive uptake coefficients (γ ). The aerosol experiments (Saharan dust only) indicated efficient uptake, with e.g. a value of γ (SDCV)=(1.3±0.2)×10 −2 obtai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(115 citation statements)
references
References 60 publications
4
104
7
Order By: Relevance
“…The kinetics of the uptake of N 2 O 5 onto desert dust particles and their surrogates (e.g., Arizona Test Dust, illite) has been reported by several previous studies (Karagulian et al, 2006;Mogili et al, 2006;Seisel et al, 2005;Tang et al, 2010Tang et al, , 2012Tang et al, , 2014Wagner et al, 2008Wagner et al, , 2009). In addition, Seisel et al (2005) observed the formation of nitrate on mineral dust particles due to the uptake of N 2 O 5 using diffuse reflectance FTIR (Fourier transform infrared spectroscopy), and Tang et al (2012) further confirmed that the yield of nitrate is ∼ 2 (as expected from Reaction R1) within the experimental uncertainty, and that the formation of NO 2 is negligible.…”
Section: Introductionmentioning
confidence: 59%
See 4 more Smart Citations
“…The kinetics of the uptake of N 2 O 5 onto desert dust particles and their surrogates (e.g., Arizona Test Dust, illite) has been reported by several previous studies (Karagulian et al, 2006;Mogili et al, 2006;Seisel et al, 2005;Tang et al, 2010Tang et al, , 2012Tang et al, , 2014Wagner et al, 2008Wagner et al, , 2009). In addition, Seisel et al (2005) observed the formation of nitrate on mineral dust particles due to the uptake of N 2 O 5 using diffuse reflectance FTIR (Fourier transform infrared spectroscopy), and Tang et al (2012) further confirmed that the yield of nitrate is ∼ 2 (as expected from Reaction R1) within the experimental uncertainty, and that the formation of NO 2 is negligible.…”
Section: Introductionmentioning
confidence: 59%
“…The glass reactor used in this work has a volume of ∼ 30 cm 3 (with a length of 10 cm and an inner diameter of 2 cm), leading to a residence time of ∼ 3 s at a flow rate of ∼ 500 mL min −1 . At atmospheric pressure and 90 • C, the lifetime of N 2 O 5 with respect to thermal decomposition (Reaction R4b) is around ∼ 0.05 s and the lifetime of NO 3 radicals due to the titration by 1 ppmv NO (Reaction R5) is ∼ 0.002 s, as detailed by Wagner et al (2008). The residence time in the reactor is much longer than the lifetime of N 2 O 5 and NO 3 under our experimental condition, ensuring that all the N 2 O 5 should be decomposed and then titrated by NO.…”
Section: N 2 O 5 Detectionmentioning
confidence: 86%
See 3 more Smart Citations